2010
DOI: 10.1074/jbc.m110.122069
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between Wnt3a and Heparin Enhances Osteogenesis via a Phosphoinositide 3-Kinase/Akt/RUNX2 Pathway

Abstract: A new strategy has emerged to improve healing of bone defects using exogenous glycosaminoglycans by increasing the effectiveness of bone-anabolic growth factors. Wnt ligands play an important role in bone formation. However, their functional interactions with heparan sulfate/heparin have only been investigated in non-osseous tissues. Our study now shows that the osteogenic activity of Wnt3a is cooperatively stimulated through physical interactions with exogenous heparin. N-Sulfation and to a lesser extent O-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 60 publications
2
69
2
Order By: Relevance
“…2D). WntA heterozygosity is predicted to spread WntA distribution by driving its expression in adjacent domains, and similarly, heparin injections are expected to promote Wntligand spread (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The comparable outcomes of heparin injections and WntA heterozygosity thus suggest that heparininduced pattern expansions are largely mediated by WntA (SI Appendix, Fig.…”
Section: Wnta Expression Is Variable and Marks Presumptive Black Pattmentioning
confidence: 76%
See 1 more Smart Citation
“…2D). WntA heterozygosity is predicted to spread WntA distribution by driving its expression in adjacent domains, and similarly, heparin injections are expected to promote Wntligand spread (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The comparable outcomes of heparin injections and WntA heterozygosity thus suggest that heparininduced pattern expansions are largely mediated by WntA (SI Appendix, Fig.…”
Section: Wnta Expression Is Variable and Marks Presumptive Black Pattmentioning
confidence: 76%
“…Heparin is an analog of heparan sulfate proteoglycans, a class of extracellular matrix compounds that play a key role in morphogen gradient formation (32). In particular, heparin-like chains bind Wntfamily ligands and promote their mobility in epithelial tissues, resulting in the expansion of their extracellular gradients (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). There is precedent for this effect in the butterfly Junonia coenia, where heparin injections resulted in specific expansions of the wing patterns associated with wingless expression (30,42).…”
Section: Wnta Expression Is Variable and Marks Presumptive Black Pattmentioning
confidence: 99%
“…(63) PIK3R1 encodes a subunit of phosphatidylinositol 3 kinase, which is an important mediator in both osteoblast and osteoclast differentiation. (64)(65)(66)(67) Although no known function of PRKCH (protein kinase C, eta) and SCNN1B (epithelial sodium channel) is reported in any bone cell or bone diseases, gene expression of PRKCH in osteoblasts is correlated with other bone markers (ie, osteocalcin, bone sialoprotein, and alkaline phosphatase) at various differentiation and maturation stages, (68) suggesting that PRKCH is a potential candidate gene that affects bone metabolism. The second most significant canonical pathway associated with the gene clusters was the pathway responsible for rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 99%
“…Double transfection of Wnt3a plasmid and Wnt9a siRNA resulted in a significant increase in the ALP activity and the expression of Runx2, suggesting its stimulatory role in early osteoblast differentiation. These findings suggest that Wnt3a and Wnt9a could act as potential novel therapeutic targets for re-building bone, as has recently been reported for the synergism between Wnt3a and other osteogenic factors, such as BMP and heparin [36,37]. Moreover, a previous study showed that canonical Wnt signaling stimulated the expression of Runx2 and OC in a SFRP1-null mouse (secreted frizzled-related protein-1), which exhibited activated Wnt signaling and a high bone mass phenotype [38].…”
Section: Discussionmentioning
confidence: 89%